High-impact high-gloss ASA resin and preparation method thereof
By adopting specific graft copolymer ASA glue powder and preparation methods, the problem of difficult balance between gloss and impact strength of ASA resin is solved, and the high gloss and high impact strength is achieved, and it is suitable for automobiles and other fields.
Patent Information
- Application Number
- CN202510045154.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
AI Technical Summary
Existing ASA resins are difficult to achieve a balance between improving gloss and impact strength, and high gloss usually lead to a decrease in impact strength, limiting their application in the automotive field.
A graft copolymer ASA glue powder containing 50 to 80 mass % of graft matrix A1 and 20 to 50 mass % of graft shell A2 is used, and the ASA glue powder is obtained by a specific preparation method, including adding butyl acrylate, emulsifier, crosslinking agent, electrolyte and water to the reactor, nitrogen gas, mixing and insulating, followed by addition of initiators and other monomers, and gradually preparing the ASA latex, and finally obtaining the ASA glue powder by coagulation, dehydration, washing and drying, and blending it with the thermoplastic copolymer SAN to prepare the ASA resin.
It achieves the balance of high gloss and high impact strength of ASA resin, with impact strength exceeding 400J/m and gloss exceeding 90, and is suitable for automobiles and other fields.
Smart Images

Figure BDA0005238176020000111 
Figure HDA0005238176030000011 
Figure HDA0005238176030000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymers, and in particular relates to a high-impact and high-gloss ASA resin and a preparation method thereof. Background Art
[0002] ASA resin is an engineering plastic with excellent performance. It is grafted copolymerized by three monomers: acrylonitrile, butyl acrylate and styrene. It has a core-shell structure. The polybutyl acrylate rubber phase is the core, which can play a toughening effect and provide impact resistance for the resin. Styrene-acrylonitrile resin (SAN) is the shell, which enhances the compatibility of the dispersed phase and the continuous phase.
[0003] The rubber phase in ASA resin is polybutyl acrylate, and the rubber has large cohesive energy. It is difficult to induce silver streaks and cavitation when impacted. The rubber has poor elasticity and low toughening efficiency, and the ASA resin has poor impact resistance. At the same time, with the vigorous promotion of new energy vehicles, the appearance of cars tends to have high gloss and cool effects, which also requires the gloss of ASA resin. The existing method to improve the gloss of ASA resin is to blend ASA with PMMA, but the improvement of the gloss of ASA resin is limited, and it will also reduce the impact resistance of the material, limiting its application in the automotive field.
[0004] The preparation method of high-impact ASA generally adopts the mixing of large and small particle sizes. For example, Wu Kunpeng et al. (The influence of rubber particle size and its synergistic effect on ASA toughened SAN resin, Wu Kunpeng, Yu Jinshuo, Kong Lei, 2023) use 100nm ASA rubber powder and 600nm ASA rubber powder to mix in a certain proportion to prepare high-impact ASA resin with an impact strength of up to 600J / m. The rubber powder is added in large amounts - 50 parts by mass. Large particle size plus excessive rubber powder addition will reduce the gloss of the resin. Patent CN119143944A mentions the introduction of an inorganic nano-silica core and an organic silicon transition layer into a polybutyl acrylate core to enhance the impact resistance of the resin. This method involves four polymerization steps, and the preparation process is relatively cumbersome. The final impact resistance of the resin is only 21.5-22.9 MPa, and the glossiness of the resin is not improved. The structure of the ASA prepared in patent CN116640271A is a PBA core-high molecular weight micro-crosslinked SAN shell-SAN shell with the same molecular weight as the blended SAN. Micro-crosslinking of SAN resin will cause the particles to be hard, and often cannot bring a high toughening effect. The impact strength of the prepared ASA resin is only 15 kJ / m 2, which is only the performance level of ordinary ASA resin; in addition to adding cross-linking monomers, patent CN109867749A also increases the grafting rate by adding reactive end groups to PBA / adding epoxy groups to SAN, but the increase in grafting sites will lead to a shorter chain length of the shell SAN molecule, a difference in molecular weight with the matrix SAN, and poor compatibility. The impact strength of ASA resin is only 180J / m, which is only the performance level of ordinary ASA resin.
[0005] In summary, the gloss and impact strength of ASA resin cannot be taken into account at the same time, and it is difficult to achieve a balance between high gloss and high impact. Summary of the invention
[0006] In view of the above problems existing in the prior art, one of the purposes of the present invention is to provide a method for preparing graft copolymer ASA rubber powder. On the one hand, small particle size rubber is conducive to improving glossiness, and on the other hand, the inclusions contained in the rubber core can effectively improve the rubber toughening effect and the reflection intensity of light.
[0007] A second object of the present invention is to provide a method for preparing an ASA resin, wherein the resin has high gloss and high impact strength.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0009] In the first aspect, the present invention provides a high-impact and high-gloss ASA resin, comprising the following components: a thermoplastic copolymer SAN and a graft copolymer ASA rubber powder, wherein the graft copolymer ASA rubber powder comprises 50 to 80% by mass of a graft base A1 and 20 to 50% by mass of a graft shell layer A2, wherein the graft base A1 contains inclusions, and the content of the inclusions is 5-40% based on the mass of A1.
[0010] In one embodiment of the present invention, the graft base A1 comprises polybutyl acrylate rubber.
[0011] In one embodiment of the present invention, the graft shell layer A2 is a copolymer of styrene and acrylonitrile (SAN), or a copolymer of styrene, acrylonitrile and methyl methacrylate (MSAN).
[0012] In one embodiment of the present invention, the inclusions are SAN and / or MSAN.
[0013] In a second aspect, the present invention provides a method for preparing an ASA latex, comprising the steps of:
[0014] S1: Add butyl acrylate, emulsifier, crosslinking agent, electrolyte and water into a reactor, introduce nitrogen, mix and keep warm;
[0015] S2: adding an initiator to the product of S1 to react and prepare a seed emulsion;
[0016] S3: adding butyl acrylate, a crosslinking agent, an emulsifier, water, and an initiator dropwise to the product of S2, and keeping the temperature to prepare a PBA emulsion;
[0017] S4: adding styrene, acrylonitrile, optional methyl methacrylate, a reducing agent and an initiator to the S3 product;
[0018] S5: Add styrene, acrylonitrile, optional methyl methacrylate, emulsifier, water and initiator dropwise to the product of S4, and keep the mixture warm to prepare ASA latex.
[0019] In one embodiment of the present invention, in S1, butyl acrylate comprises 1-4 parts by mass, emulsifier comprises 0.002-0.04 parts by mass, cross-linking agent comprises 0-0.2 parts by mass, electrolyte comprises 0-0.8 parts by mass, and water comprises 30-80 parts by mass.
[0020] In one embodiment of the present invention, in S1, the emulsifier is an anionic emulsifier, preferably one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, potassium oleate, potassium disproportionated rosin acid and dioctyl sodium sulfosuccinate.
[0021] In one embodiment of the present invention, in S1, the crosslinking agent is a multifunctional monomer, preferably one or more of divinylbenzene, allyl methacrylate, ethylene glycol acrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, triallyl isocyanurate, triallyl cyanurate, diallyl maleate, and dicyclopentadienyl acrylate.
[0022] In one embodiment of the present invention, in S1, the electrolyte is an inorganic salt, preferably one or more of potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, and sodium tripolyphosphate.
[0023] In one embodiment of the present invention, in S1, the insulation temperature is 40°C-70°C.
[0024] In one embodiment of the present invention, in said S2, the initiator is 0.002-0.02 parts by mass.
[0025] In one embodiment of the present invention, in S2, the initiator is selected from inorganic peroxides and / or organic peroxides, preferably one or more of potassium persulfate, sodium persulfate, ammonium persulfate, dicumyl peroxide, and cumyl hydroperoxide.
[0026] In one embodiment of the present invention, in said S2, the reaction time is 0.5-1h.
[0027] In one embodiment of the present invention, in S3, butyl acrylate is 49-76 parts by mass, emulsifier is 0.15-0.75 parts by mass, cross-linking agent is 0.2-3.8 parts by mass, water is 50-80 parts by mass, and initiator is 0.05-2 parts by mass.
[0028] In one embodiment of the present invention, in S3, the emulsifier is an anionic emulsifier, preferably one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, potassium oleate, potassium disproportionated rosin acid and dioctyl sodium sulfosuccinate.
[0029] In one embodiment of the present invention, in S3, the crosslinking agent is a multifunctional monomer, preferably one or more of divinylbenzene, allyl methacrylate, ethylene glycol acrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, triallyl isocyanurate, triallyl cyanurate, diallyl maleate, and dicyclopentadienyl acrylate.
[0030] In one embodiment of the present invention, in S3, the initiator is selected from inorganic peroxides and / or organic peroxides, preferably one or more of potassium persulfate, sodium persulfate, ammonium persulfate, dicumyl peroxide, and cumyl hydroperoxide.
[0031] In one embodiment of the present invention, in said S3, the dropping time is 2-5h.
[0032] In one embodiment of the present invention, in said S3, the insulation time is 1-2h.
[0033] In one embodiment of the present invention, in the S4, styrene is 3-8 parts by mass, acrylonitrile is 1-3 parts by mass, methyl methacrylate is 0-3 parts by mass, reducing agent is 0.02-0.06 parts by mass, and initiator is 0.03-0.1 parts by mass.
[0034] In one embodiment of the present invention, in S4, the reducing agent is preferably one or more of ferrous sulfate, glucose, sodium pyrophosphate, sodium pyrophosphate, and EDTA.
[0035] In one embodiment of the present invention, in S4, the initiator is selected from organic peroxides, preferably one or more of tert-butyl hydroperoxide, diisopropylbenzene peroxide, and cumene hydroperoxide.
[0036] In one embodiment of the present invention, in the S5, styrene is 12-22 parts by mass, acrylonitrile is 4-7 parts by mass, methyl methacrylate is 0-7 parts by mass, emulsifier is 0.3-1 parts by mass, water is 50-100 parts by mass, and initiator is 0.15-0.5 parts by mass.
[0037] In one embodiment of the present invention, in S5, the emulsifier is an anionic emulsifier, preferably one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, potassium oleate, potassium disproportionated rosin acid and dioctyl sodium sulfosuccinate.
[0038] In one embodiment of the present invention, in S5, the initiator is selected from organic peroxides, preferably one or more of tert-butyl hydroperoxide, dicumyl peroxide, and cumyl hydroperoxide.
[0039] In one embodiment of the present invention, in said S5, the dropping time is 2-5h.
[0040] In one embodiment of the present invention, in said S5, the insulation time is 1-3h.
[0041] The present invention also provides a method for preparing graft copolymer ASA rubber powder, comprising the following steps: 100 parts by weight of the ASA latex on a dry basis of the present invention is coagulated and demulsified with 2-4 parts by weight of calcium chloride, and then washed and dried to prepare the powder.
[0042] As a scheme, in the present invention, the ASA latex of the present invention is coagulated, dehydrated, washed, and dried to obtain ASA rubber powder, and then mixed with a thermoplastic copolymer and extruded to obtain ASA resin, which is a conventional technique in the art. Those skilled in the art can perform combination screening according to actual needs, and the present invention will not repeat them in detail.
[0043] Another object of the present invention is to provide a use of a high-impact and high-gloss ASA resin, wherein the ASA resin is used in the fields of automobiles, home appliances, office supplies, etc., preferably in the automobile field.
[0044] Compared with the prior art, the technical solution of the present invention has the beneficial effect that: the present invention uses a core-shell structure polymer containing 1-40 weight % inclusions in the rubber phase and blends it with a thermoplastic resin SAN to prepare an ASA resin, and the ASA resin has excellent impact strength and gloss. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 TEM image of the ASA latex provided in Example 1;
[0046] Figure 2 This is the TEM image of ASA latex provided for Comparative Example 2. DETAILED DESCRIPTION
[0047] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0048] Unless otherwise specified, the raw materials used in the following examples and comparative examples of the present invention are obtained from commercial channels.
[0049] Butyl acrylate, produced in Wanhua Chemical Industrial Park;
[0050] Sodium lauryl sulfate, 99% purchased from Aladdin;
[0051] Cumene hydroperoxide, 80%, purchased from Aladdin;
[0052] tert-Butyl hydroperoxide, 70%, purchased from Aladdin;
[0053] Potassium oleate, BM-400, was purchased from Ino Reagent;
[0054] Ferrous sulfate, 99%, purchased from Xilong Chemical;
[0055] Glucose, 99%, purchased from Xilong Chemical;
[0056] Sodium pyrophosphate, 99%, purchased from Aladdin;
[0057] Allyl methacrylate, 99%, purchased from Aladdin;
[0058] Acrylonitrile, 99%, purchased from Aladdin;
[0059] Styrene, 99%, purchased from Aladdin;
[0060] Potassium carbonate, 99%, purchased from Aladdin.
[0061] The following test method is used in the embodiments of the present invention:
[0062] Latex particle size: The latex was diluted 20,000 times with deionized water, and the particle size was measured using a Malvern Zetasizer Nano-ZS90 particle size analyzer.
[0063] Transmission electron microscope image: ASA resin sections were stained with ruthenium tetroxide solution to observe the structure of the polymer. Transmission electron microscope (TEM) manufacturer: Thermo Fisher, model: Talos F200c.
[0064] Inclusion content: The volume ratio of inclusions to polybutyl acrylate is calculated by using a statistical algorithm through the TEM image, and then multiplied by the density ratio of the inclusions to polybutyl acrylate to obtain the mass content of the inclusions.
[0065] Mechanical properties: Izod notched impact test standard ASTM D256, 23°C, using Italian CEAST 9050.
[0066] Gloss: 60° gloss tested using ASTM D523, BYK-Gardner GmbH.
[0067] Example 1
[0068] 3 parts by mass of butyl acrylate, 0.01 parts by mass of sodium dodecyl sulfate, 0.1 parts by mass of allyl methacrylate, 0.5 parts by mass of potassium carbonate and 50 parts by mass of deionized water were added to the reactor, nitrogen was introduced, mixed and kept warm at 50° C. 0.015 parts by mass of potassium persulfate was added to the reactor, reacted for 0.6 hours, and a seed emulsion was prepared.
[0069] 60 parts by mass of butyl acrylate, 2 parts by mass of allyl methacrylate, 0.5 parts by mass of sodium dodecyl sulfate, 60 parts by mass of water and 1 part by mass of sodium persulfate were added dropwise to the reactor for 3 hours and the heat preservation time was 1.5 hours to prepare a PBA emulsion.
[0070] Add 5 parts by mass of styrene, 2 parts by mass of acrylonitrile, 1 part by mass of methyl methacrylate, 0.04 parts by mass of ferrous sulfate / bleaching powder and 0.05 parts by mass of tert-butyl hydroperoxide into a reactor; then dropwise add 15 parts by mass of styrene, 5 parts by mass of acrylonitrile, 5 parts by mass of methyl methacrylate, 0.5 parts by mass of sodium lauryl sulfate, 70 parts by mass of water and 0.3 parts by mass of cumene hydroperoxide into the reactor, the dropping time is 3 hours, and the insulation time is 2 hours to prepare ASA latex.
[0071] Example 2
[0072] 1 part by mass of butyl acrylate, 0.002 parts by mass of sodium dodecylbenzene sulfonate, 0.2 parts by mass of divinylbenzene, 0.8 parts by mass of potassium bicarbonate and 30 parts by mass of deionized water were added to a reactor, nitrogen was introduced, mixed and kept warm at 40° C. 0.002 parts by mass of sodium persulfate was added to the reactor, reacted for 0.5 hours, and a seed emulsion was prepared.
[0073] 49 parts by mass of butyl acrylate, 0.2 parts by mass of divinylbenzene, 0.15 parts by mass of sodium dodecylbenzene sulfonate, 50 parts by mass of water and 0.05 parts by mass of potassium persulfate were added dropwise to the reactor for 2 hours and the heat preservation time was 1 hour to prepare a PBA emulsion.
[0074] 3 parts by mass of styrene, 1 part by mass of acrylonitrile, 0.02 parts by mass of glucose / sodium pyrophosphate and 0.03 parts by mass of diisopropylbenzene hydroperoxide were added into a reactor; then 12 parts by mass of styrene, 4 parts by mass of acrylonitrile, 0.3 parts by mass of potassium disproportionate rosin acid, 50 parts by mass of water and 0.15 parts by mass of tert-butyl hydroperoxide were dropwise added into the reactor for 2 hours and the insulation time was 1 hour to prepare ASA latex.
[0075] Example 3
[0076] 4 parts by mass of butyl acrylate, 0.02 parts by mass of potassium disproportionate rosin acid and 80 parts by mass of deionized water were added to the reactor, nitrogen was introduced, mixed and kept warm at 70° C. 0.02 parts by mass of ammonium persulfate was added to the reactor and reacted for 1 hour to prepare a seed emulsion.
[0077] 76 parts by mass of butyl acrylate, 3.8 parts by mass of triallyl isocyanurate, 0.75 parts by mass of potassium disproportionated rosin acid, 80 parts by mass of water and 2 parts by mass of cumene hydroperoxide were added dropwise to the reactor for 5 hours and the heat preservation time was 2 hours to prepare a PBA emulsion.
[0078] 8 parts by mass of styrene, 3 parts by mass of acrylonitrile, 3 parts by mass of methyl methacrylate, 0.06 parts by mass of glucose and 0.1 parts by mass of cumene hydroperoxide were added into a reactor; then 22 parts by mass of styrene, 7 parts by mass of acrylonitrile, 7 parts by mass of methyl methacrylate, 1 part by mass of potassium oleate, 100 parts by mass of water and 0.5 parts by mass of cumene hydroperoxide were dropwise added into the reactor for 5 hours and the insulation time was 3 hours to prepare ASA latex.
[0079] Example 4
[0080] 2 parts by mass of butyl acrylate, 0.04 parts by mass of potassium oleate, 0.05 parts by mass of triallyl cyanuric acid, 0.3 parts by mass of sodium bicarbonate and 60 parts by mass of deionized water were added to the reactor, nitrogen was introduced, mixed and kept warm at 60° C. 0.01 parts by mass of cumene hydroperoxide was added to the reactor, and the reaction was carried out for 0.8 hours to prepare a seed emulsion.
[0081] 65 parts by mass of butyl acrylate, 1.5 parts by mass of triallyl cyanuric acid, 0.4 parts by mass of potassium oleate, 70 parts by mass of water and 1.5 parts by mass of cumene hydroperoxide were added dropwise to the reactor for 4 hours and the heat preservation time was 2 hours to prepare a PBA emulsion.
[0082] Add 6 parts by mass of styrene, 1.5 parts by mass of acrylonitrile, 2 parts by mass of methyl methacrylate, 0.05 parts by mass of ferrous sulfate / EDTA and 0.08 parts by mass of tert-butyl hydroperoxide into a reactor; then add 18 parts by mass of styrene, 6 parts by mass of acrylonitrile, 3 parts by mass of methyl methacrylate, 0.7 parts by mass of sodium dodecylbenzene sulfonate, 80 parts by mass of water and 0.2 parts by mass of diisopropylbenzene hydroperoxide dropwise into the reactor, the dropping time is 4 hours, and the insulation time is 2.5 hours to prepare ASA latex.
[0083] Comparative Example 1
[0084] Compared with Example 1, the difference is that the grafting monomer is added in its entirety at the bottom during the first addition, and the rest is the same as Example 1.
[0085] Comparative Example 2
[0086] Compared with Example 1, the difference is that no grafting monomer is added during the first addition, and all the grafting monomer is used for the second dropwise addition. The rest is the same as Example 1.
[0087] According to the following steps, the ASA latex prepared in the examples and comparative examples was used to prepare ASA rubber powder, and the mixture was blended with SAN resin and extruded and injection molded into test specimens for testing:
[0088] 1) Preparation of ASA rubber powder
[0089] 1.5 kg of calcium chloride and 200 kg of deionized water were added to the coagulation kettle and stirring was started to fully dissolve the calcium chloride. The coagulation kettle was heated to 75° C. 100 kg of the ASA latex prepared in the embodiment or the comparative example was added to the coagulation kettle in a continuous feeding manner for 1 hour. After the feeding was completed, the coagulation kettle was heated to 90° C. and kept warm for 1 hour. The coagulation kettle was cooled to room temperature and the coagulation slurry was filtered, washed and dehydrated to obtain ASA wet rubber powder. The ABS wet rubber powder was dried at 65° C. in a fluidized bed dryer to a water content of <1% to obtain ASA rubber powder.
[0090] 2) ASA resin preparation, injection molding and performance testing
[0091] A twin-screw extruder was used, and the three-stage temperatures were 190° C., 210° C. and 220° C., respectively. SAN resin with the brand name SA30 of LG Chemical was used as the blending continuous phase, and the ASA rubber powder prepared in step 1) (calculated based on the polybutylene acrylate rubber content of 24wt% in the ASA resin) was used as the blending dispersed phase. Blending, extrusion and granulation were performed to obtain the ASA resin.
[0092] The ASA resin was used to prepare various test specimens at 210° C. on an injection molding machine, and the gloss and impact strength of the ASA resin were tested according to ASTM D1925 and ASTM D256 standards, respectively.
[0093] Table 1 PBA / ASA particle size and ASA resin properties prepared in Examples and Comparative Examples
[0094]
[0095] It can be seen from the test results of Examples 1-4 and Comparative Examples 1-2 that, compared with the ASA resin prepared from the ASA latex prepared in the comparative example, the ASA resin prepared from the ASA latex prepared in the present invention has better impact strength (>400 J / m) and higher gloss (>90).
[0096] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A high-impact and high-gloss ASA resin, comprising the following components: a thermoplastic copolymer SAN and a graft copolymer ASA rubber powder, wherein the graft copolymer ASA rubber powder comprises 50 to 80% by mass of a graft base A1 and 20 to 50% by mass of a graft shell layer A2, wherein the graft base A1 contains inclusions, and the content of the inclusions is 5-40% based on the mass of A1.
2. The ASA resin according to claim 1, characterized in that The inclusions are SAN or MSAN.
3. The ASA resin according to claim 1 or 2, characterized in that The graft base A1 comprises polybutyl acrylate rubber.
4. The ASA resin according to any one of claims 1 to 3, characterized in that The graft shell layer A2 is SAN or MSAN.
5. The ASA resin according to any one of claims 1 to 4, characterized in that The preparation method of ASA latex for preparing ASA rubber powder comprises the following steps: S1: Add butyl acrylate, emulsifier, crosslinking agent, electrolyte and water into the reactor, introduce nitrogen, mix and keep warm; S2: adding an initiator to the product of S1 to react and prepare a seed emulsion; S3: adding butyl acrylate, a crosslinking agent, an emulsifier, water, and an initiator dropwise to the product of S2, and keeping the temperature to prepare a PBA emulsion; S4: adding styrene, acrylonitrile, optional methyl methacrylate, a reducing agent and an initiator to the S3 product; S5: Add styrene, acrylonitrile, optional methyl methacrylate, emulsifier, water and initiator dropwise to the product of S4, and keep the mixture warm to prepare ASA latex.
6. The ASA resin according to claim 5, characterized in that In the S1, butyl acrylate is 1-4 parts by mass, emulsifier is 0.002-0.04 parts by mass, cross-linking agent is 0-0.2 parts by mass, electrolyte is 0-0.8 parts by mass, and water is 30-80 parts by mass.
7. The ASA resin according to claim 5 or 6, characterized in that In the S3, butyl acrylate is 49-76 parts by mass, emulsifier is 0.15-0.75 parts by mass, cross-linking agent is 0.2-3.8 parts by mass, water is 50-80 parts by mass, and initiator is 0.05-2 parts by mass.
8. The ASA resin according to any one of claims 5 to 7, characterized in that In the S4, styrene is 3-8 parts by mass, acrylonitrile is 1-3 parts by mass, methyl methacrylate is 0-3 parts by mass, a reducing agent is 0.02-0.06 parts by mass, and an initiator is 0.03-0.1 parts by mass.
9. The ASA resin according to any one of claims 5 to 8, characterized in that In the S5, styrene is 12-22 parts by mass, acrylonitrile is 4-7 parts by mass, methyl methacrylate is 0-7 parts by mass, emulsifier is 0.3-1 parts by mass, water is 50-100 parts by mass, and initiator is 0.15-0.5 parts by mass.
10. A method for preparing the high-impact and high-gloss ASA resin according to any one of claims 1 to 9, comprising the following steps: 100 parts by weight of dry basis ASA latex is coagulated by 2-4 parts by weight of calcium chloride, dehydrated, washed and dried to prepare ASA rubber powder; the ASA rubber powder is blended with SAN resin and extruded.
Citation Information
Patent Citations
Acrylate-styrene-acrylonitrile grafted copolymer and production method thereof
CN109867749A
Acrylate graft copolymer with core-shell-shell structure and preparation method thereof
CN116640271A
High-impact ASA high rubber powder for automobiles
CN119143944A
Preparation method of ASA resin
CN113150460A
Grafting latex for high-impact-resistance and high-weather-resistance ASA resin as well as preparation method and application of grafting latex
CN118909199A